The PduM Protein Is a Structural Component of the Microcompartments Involved in Coenzyme B(12)-Dependent 1,2-Propanediol Degradation by Salmonella enterica - Sinha, Sharmistha (American Society for Microbiology, 2012)
Diverse bacteria use proteinaceous microcompartments (MCPs) to optimize metabolic pathways that have toxic or volatile intermediates. MCPs consist of metabolic enzymes encased within a protein shell that provides a defined environment. In Salmonella enterica, a MCP is involved in B(12)-dependent 1,2-propanediol utilization (Pdu MCP). In this report, we show that the protein PduM is required for the assembly and function of the Pdu MCP. The results of tandem mass spectrometry and Western blot analyses show that PduM is a component of the Pdu MCP. Electron microscopy shows that a pduM deletion mutant forms MCPs with abnormal morphology. Growth tests and metabolite measurements establish that a pduM deletion mutant is unable to form functional MCPs. PduM is unrelated in sequence to proteins of known function and hence may represent a new class of MCP structural proteins. We also report a modified protocol for the purification of Pdu MCP from Salmonella which allows isolation of milligram amounts of MCPs in about 4 h. We believe that this protocol can be extended or modified for the purification of MCPs from diverse bacteria.